Call down the hawk - Stiefvater, Maggie, 1981- (Stiefvater, Maggie, 1981- Dreamer trilogy, 2019)
Ronan Lynch is a dreamer. He can pull both curiosities and catastrophes out of his dreams and into his compromised reality. Jordan Hennessy is a thief. The closer she comes to the dream object she is after, the more inextricably she becomes tied to it. Carmen Farooq-Lane is a hunter. Her brother was a dreamer . . . and a killer. She has seen what dreaming can do to a person. And she has seen the damage that dreamers can do. But that is nothing compared to the destruction that is about to be unleashed.